HUBUNGAN ANTARA REINFORCEMENT (POSITIF DAN NEGATIF) DALAM PEMBELAJARAN DARING DENGAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI SMAN 22 BANDUNG - Selvina Januarista, - (2022)
The study, titled "The Relationship Between Reinforcement and Punishment in Online Learning with Student Learning Motivation in Mathematics Subjects at SMAN 22 Bandung," was carried out as a result of the implementation of online learning, which affects student motivation, particularly in mathematics subjects, which are declining, and is supported by students' assumptions about mathematics, which assumes it is difficult and confusing. Reinforcement (both positive and negative reinforcement) is viewed as an educational tool with a close relationship to motivation because it can increase students' external motivation in learning. Motivation is essential for a student to achieve learning success, particularly in online learning. The research question is whether there is a positive and significant relationship between reinforcement and punishment with student learning motivation in online mathematics subjects at SMAN 22 Bandung. This study employs quantitative correlational research methods. The participants in this study were students from SMAN 22 Bandung's class XI Science. Simple random sampling was used as the sampling technique. This study's sample consists of 65 students from SMAN 22 Bandung's . This study used a questionnaire to collect data. According to the findings of this study, the provision of reinforcement with the motivation to learn mathematics has a coefficient value of 0.511 and a significance value of 0.000, indicating that it is has positive relationship. Then, with a coefficient value of 0.288 and a significance value of 0.020, the reinforcement of punishment with motivation to learn mathematics has a sufficient and significant relationship. The provision of reinforcement and punishment with the motivation to learn mathematics has a coefficient value of 0.541 and a significance value of 0.000 in the multiple correlation test, indicating that it has a strong and significant relationship. Keywords: Reinforcement, Punishment, Learning Motivation